A Technical Approach to the Traditional Sport of Hadang in Improving the Motor Ability of Elementary School Students - Prasetio, Pajar Anugrah; Simbolon, Marlina Eliyanti; Iskandar, Aldi Nurhadiat (PrimaryEdu : Journal of Primary Education, 2024)
This research was conducted to find out the increase in motor ability during the pretest and then, given the learning of traditional sports with a technical approach, namely, an approach that emphasizes actual game techniques, look at the results of the pretest to see if there is an increase in students' motor abilities in the components of speed, endurance, agility, hand-eye coordination, and balance. The method used in this study is the pre-experimental design method. The population in this study was all upper-class students at Kuningan Elementary School. A total of 23 students from IV-B were selected as the research sample through the purposive sampling technique. The data collection techniques used in this study were tests and measurements. The research began with a warm-up, a pre-test, giving directions and training treatments using a technical approach, and then after being given treatment, a final test (a post-test) of the motor ability test was carried out. The study's findings from data analysis show that training in traditional hadang sports using a technical approach has a significant effect on improving motor ability skills in high school and elementary school students at SDN 11 Kuningan.